ANALISIS PENYEBAB MACETNYA PINJAMAN KONSUMEN PADA KOPERASI ASKES (KOPKARKES) LAMPUNG KECAMATAN KEMILING BANDAR LAMPUNG TAHUN 2015 - Narulita, Sari (LPPM STKIP PGRI Bandar Lampung, 2016)
The employees cooperative of Askes Lampung is a branch under the supervision of credit and saving of PT.ASKES which is located in Bandar Lampung. The problems encountered in this company is to know the cause of the breakdown of consumer loans Employees Cooperative Askes Lampung by analyzing the financial statements of loans in 2015. This may be due to various factors or deliberate consumers. So the author takes the title